Overlap between pdxA and ksgA in the complex pdxA-ksgA-apaG-apaH operon of Escherichia coli K-12. - Roa, B B (1989)
We report that pdxA, which is required for de novo biosynthesis of pyridoxine (vitamin B6) and pyridoxal phosphate, belongs to an unusual, multifunctional operon. The pdxA gene was cloned in the same 3.5-kilobase BamHI-EcoRI restriction fragment that contains ksgA, which encodes the 16S rRNA modification enzyme m6(2)A methyltransferase, and apaH, which encodes diadenosine tetraphosphatase (ApppA hydrolase). Previously, Blanchin-Roland et al. showed that ksgA and apaH form a complex operon (Mol. Gen. Genet. 205:515-522, 1986). The pdxA gene was located on recombinant plasmids by subcloning, complementation, and insertion mutagenesis, and chromosomal insertions at five positions upstream from ksgA inactivated pdxA function. DNA sequence analysis and minicell translation experiments demonstrated that pdxA encoded a 35.1-kilodalton polypeptide and that the stop codon of pdxA overlapped the start codon of ksgA by 2 nucleotides. The translational start codon of pdxA was tentatively assigned based on polypeptide size and on the presence of a unique sequence that was also found near the translational start of PdxB. This conserved sequence may play a role in translational control of certain pyridoxine biosynthetic genes. RNase T2 mapping of chromosomal transcripts confirmed that pdxA and ksgA were members of the same complex operon, yet about half of ksgA transcripts arose in vivo under some culture conditions from an internal promoter mapped near the end of pdxA. Transcript analysis further suggested that pdxA is not the first gene in the operon. These structural features support the idea that pyridoxine-biosynthetic genes are members of complex operons, perhaps to interweave coenzyme biosynthesis genetically with other metabolic processes. The results are also considered in terms of ksgA expression.